Highlights from the ILRI annual Report 2003 - International Livestock Research Institute (International Livestock Research Institute, 2004)
The role that partnership has played in enabling its global impacts is highlighted in this Report. ILRI collaborates with a wealth of institutions at national, regional and international levels. An example of partnership at each level is highlighted. The examples Reported are, 1) Poverty mapping with national partners in East Africa that has led to the production of high resolution poverty maps that are already proving invaluable in helping policy makers design pro-poor interventions; 2) CASREN, the Crop-Animal Systems Research Network which is a regional project in Southeast Asia coordinated by ILRI. It has worked with national and regional partners to enhance the productivity of smallholder mixed crop-and-livestock farmers; and 3) East Coast fever vaccine Development that has brought together an international consortium of partners from Africa, Europe and USA. Both private and public institutions have been involved in the research process.